The Influence of Customer Experience and Service Quality on Customer Satisfaction in Micro Culinary Businesses in Jambi City - Lestari, Suci Ayu; Octavia, Ade; Fazri, Andang (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Service towards customer satisfaction in micro culinary businesses in Jambi City. This study uses a quantitative approach with a descriptive-verificative design. The research population includes all micro culinary businesses in Jambi City, totaling 22,295 units in 2025, while the research sample consists of 100 customers selected using purposive sampling based on certain criteria. Data were collected through a questionnaire with a Likert scale. Data analysis was conducted through classical assumption tests to ensure model feasibility, followed by multiple linear regression analysis to examine the influence of each independent variable on the dependent variable. The research results indicate that customer experience has a positive and significant effect on customer satisfaction. Service quality has a positive and significant effect on customer satisfaction. Simultaneously, customer experience and service quality have a significant effect on customer satisfaction (F=50.937; p=0.000) with a coefficient of determination of 51.20%. These findings indicate that improving customer experience and service quality can be important factors in increasing customer satisfaction in micro culinary businesses in Jambi City. This study recommends that micro culinary business operators consistently improve service quality and customer experience in order to optimize customer satisfaction and business sustainability.